Repurposing Infectious Diseases Vaccines Against Cancer - Vandeborne, Liese; Pantziarka, Pan; Van Nuffel, An M. T.; Bouche, Gauthier (Frontiers in Oncology, 2021)
Vaccines used to prevent infections have long been known to stimulate immune responses to cancer as illustrated by the approval of the Bacillus Calmette–Guérin (BCG) vaccine to treat bladder cancer since the 1970s. The recent approval of immunotherapies has rejuvenated this research area with reports of anti-tumor responses with existing infectious diseases vaccines used as such, either alone or in combination with immune checkpoint inhibitors. Here, we have reviewed and summarized research activities using approved vaccines to treat cancer. Data supporting a cancer therapeutic use was found for 16 vaccines. For 10 (BCG, diphtheria, tetanus, human papillomavirus, influenza, measles, pneumococcus, smallpox, typhoid and varicella-zoster), clinical trials have been conducted or are ongoing. Within the remaining 6, preclinical evidence supports further evaluation of the rotavirus, yellow fever and pertussis vaccine in carefully designed clinical trials. The mechanistic evidence for the cholera vaccine, combined with the observational data in colorectal cancer, is also supportive of clinical translation. There is limited data for the hepatitis B and mumps vaccine (without measles vaccine). Four findings are worth highlighting: the superiority of intravesical typhoid vaccine instillations over BCG in a preclinical bladder cancer model, which is now the subject of a phase I trial; the perioperative use of the influenza vaccine to limit and prevent the natural killer cell dysfunction induced by cancer surgery; objective responses following intratumoral injections of measles vaccine in cutaneous T-cell lymphoma; objective responses induced by human papillomavirus vaccine in cutaneous squamous cell carcinoma. All vaccines are intended to induce or improve an anti-tumor (immune) response. In addition to the biological and immunological mechanisms that vary between vaccines, the mode of administration and sequence with other (immuno-)therapies warrant more attention in future research.